Strong amalgamations of lattice ordered groups and modules - Mona Cherri; Wayne B. Powell (International Journal of Mathematics and Mathematical Sciences)
We show that every variety of representable lattice ordered groups fails the strong amalgamation property. The same result holds for the variety of f-modules over an f-ring. However, strong amalgamations do occur for abelian lattice ordered groups or f-modules when the embeddings are convex.